PROJECT MANAGEMENT IN THE DIGITAL ECONOMY - Urayimov Muhammaddiyor Bakhodir ugli (Ecomind Press, 2025)
Project management in the digital economy is becoming an integral part of strategic business development, offering new opportunities to enhance efficiency and flexibility in the face of constant change. This paper examines the key aspects of project management in the digitalization era: the implementation of modern tools for process automation, the adoption of agile methodologies, the integration of data for informed decision-making, and the management of remote and distributed teams. Particular attention is paid to innovative technologies such as artificial intelligence, blockchain, and the Internet of Things, as well as to issues of data security and intellectual property protection. The article also emphasizes the importance of strategic thinking, staff training, and the development of teamwork skills. It highlights the challenges and opportunities presented by the digital economy for effective project management.
Keywords: Project management, digital economy, digitalization, agile methodologies, Agile, Scrum, Big Data, artificial intelligence, Internet of Things, blockchain, remote teams, cybersecurity, data integration, innovative technologies, business strategies, staff training, project management.